More than a matter of qualification: Teachers' thoughts on the purpose of social studies and history teaching in vocational preparation programmes in Swedish upper-secondary school. (April 2022) - Persson, Anders; Berg, Mikael
The aim of this article is to increase our understanding of how history and social studies teachers in vocational preparation programmes (VET) in Sweden relate to the obligation of preparing students for their future lives as citizens. Previous research on VET programmes has primarily emphasised predetermined roles of education. Different critical perspectives have established how different VET practices contribute to reproducing specific values and a type of knowledge that leaves less room for students to act as independent subjects. In part, the findings of this article contribute to problematising such a description. In a series of interviews, teachers expressed what can best be described as a clear will to prepare students for a future as broadminded and tolerant citizens. The multi-perspective approach emphasised by these teachers not only illustrates the socialisation and qualification functions of education, it also gives prominence to the importance of student subjectification. Furthermore, this article stresses that the teachers do not view the question of the purpose of their subjects in terms of either/or. Rather, it suggests they see their obligations as a matter of professional judgment and customised responses to unique didactic situations.